Implementasi Asesmen Perkembangan Karakter Anak Usia Dini di TK Green School Jogja - Mukaromah, Luluk (ACIECE, 2019)
This study aims to determine the Implementation of Early Childhood Development Assessmentin Jogja Green School Kindergarten. This type of research is descriptive research. When you wantto know whether the stimulation or tasks given are in accordance or not with the stages of childdevelopment. In this connection, we need accurate information about children, and this can onlybe obtained through the assessment process. The results showed that the Implementation ofPersonality Personality Character Development Assessments at TK Green School Jogja